Detrusor Arreflexia as an End Stage of Neurogenic Bladder in HAM/TSP? - Matheus Tannus; Davi Tanajura; Michael A. Sundberg; Paulo Oliveira; Neviton Castro; André Muniz Santos (Case Reports in Medicine)
The HTLV-1 virus is a known agent involved in the development of HAM/TSP. Past studies have typically observed patients with autonomic dysfunction consisting of detrusor overactivity and detrusor-sphincter dyssynergia, with the occasional observation of underactive detrusor or detrusor arreflexia. However, studies have not yet evaluated the progression of neurogenic bladder over time. In this paper, we describe a HAM/TSP patient with the initial development of overactive detrusor, and subsequent development of detrusor arreflexia. Given a paucity of studies characterizing the effects of HTLV-1 on the autonomic nervous system, particularly aspects controlling continence, this patient's clinical course may represent one type of end point for patients with HAM/TSP and neurogenic bladder. Further cohort or case-series studies, with particular emphasis on the progression of neurogenic bladder, are needed to evaluate the significance of this described case in relation to typical disease progression patterns.